Rail or plane: A pilot study on Dutch tourists' price sensitivity as a function of travel time - Matthijs Bijvoets; Jarl K. Kampen; Bas Amelung (The Central European Review of Economics and Management (CEREM), 2024)
Aim: As part of its climate and sustainability policies, the European Union actively fosters the transition from air to rail travel, for example by improving the international railway infrastructure, liberalizing the European railway market and introducing an international booking system for train travel. On the demand side, price is a crucial factor. This pilot study examines the effect of train ticket prices on holiday travel mode choice. Design/methods: In a stated preference survey targeting holiday trips from Amsterdam to eight of Europe's most popular city destinations, participants in the Netherlands were asked to choose between train and plane, given scenarios for price and travel time. Conclusion / findings: The results point to a significant correlation between price sensitivity and travel time, with price sensitivity being lowest for short and long trips and highest for medium-range trips. Originality / value of the article: The findings can inform pricing strategies of railway companies and the design of fiscal measures (taxes, subsidies) to strengthen the competitive position of European rail versus aviation.
Keywords: L92; L93; D12; R41; Q58; 330; holiday travel mode choice; train ticket price; sustainable tourism